2005
DOI: 10.1158/1078-0432.ccr-05-0729
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of RUNX3 Silencing in the Peritoneal Metastases of Gastric Cancers

Abstract: Purpose: Our previous results suggested that a lackof RUNX3 function contributed tohumangastric carcinogenesis, but the role of RUNX3 inprogression and metastasis remains unclear.We examined RUNX3 expression in clinical samples of peritoneal metastases in gastric cancers. Changes in metastatic potential were assessed in animal experiments using stable RUNX3 transfectants of gastric cancer cells. Finally, global expression changes were analyzed using a cDNA microarray. Experimental Design and Results: Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
2
60
2
Order By: Relevance
“…In one study, RUNX3 promoter methylation was detected in 75% of primary gastric carcinomas (n=22) and in 100% of cells from malignant ascites (7). However, in contrast to this previous report, in the present study, RUNX3 methylation was identified in 24.3% of primary gastric carcinomas and was not found to be increased in metastases.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In one study, RUNX3 promoter methylation was detected in 75% of primary gastric carcinomas (n=22) and in 100% of cells from malignant ascites (7). However, in contrast to this previous report, in the present study, RUNX3 methylation was identified in 24.3% of primary gastric carcinomas and was not found to be increased in metastases.…”
Section: Discussioncontrasting
confidence: 99%
“…Frequencies of the methylations of the 11 genes in corresponding non-neoplastic mucosa of the present series were similar to those reported previously (7,13,15,32), although the overall frequencies of CDH1 and TIMP3 methylation were lower than those reported previously. These findings and our findings concerning methylation frequencies in uninvolved lymph nodes, which have not been reported yet, show that CDH1, FHIT and THBS1 are methylated in a cancer-unrelated fashion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Among 45 patients with tumor invasion beyond the MP, 3 of 9 patients with methylation in any of 6 genes were diagnosed as peritoneal recurrence later while only 1 out of 35 patients without methylation in any of 6 genes developed peritoneal metastasis at least 8 months after surgery (Hiraki et al, 2011). Other potential methylation markers of peritoneal metastasis of gastric cancer include RUNX3 which was silenced by DNA methylation in 100% of peritoneal metastases of gastric cancers and 75% of primary gastric cancers but not normal gastric mucosa (Sakakura et al, 2005). In addition to detect methylated DNA in peritoneal fluids, researchers have endeavored to develop sensitive methods to quantify methy l a t e d D N A i n p e r i p h e r a l b l o o d s .…”
Section: Dna Methylation As Biomarkers For Gastric Cancermentioning
confidence: 99%